No Association Between Autonomic Functioning and Psychopathy and Aggression in Multi-Problem Young Adults - Zijlmans, Josjan; Marhe, Reshmi; van Duin, Laura; Luijks, Marie-Jolette A.; Bevaart, Floor; Popma, Arne (Frontiers in Psychology, 2021)
Abstract Background Aberrant functioning of the autonomic nervous system (ANS) is an important factor in the occurrence of antisocial behavior. Baseline autonomic functioning and the responsivity of the ANS have been related to psychopathic traits and aggression. Here we investigated whether a naturalistic sample of male multi-problem young adults (age 18-27) present with similar autonomic deficits in relation to their psychopathy and aggression as previous studies observed in clinical samples. Methods In a sample of 112 multi-problem young adults, baseline autonomic functioning and autonomic responsivity to emotional stimuli were assessed through four physiological measures: heart rate, respiratory sinus arrhythmia, pre-ejection period, and skin conductance. 27 control participants were included primarily to assess whether the task worked appropriately. Participants watched a neutral 5-minute video to assess baseline autonomic functioning and watched two sad clips to assess autonomic reactivity to sadness. We investigated the association between autonomic functioning and self-reported psychopathic traits and aggression within the multi-problem group. Results We found no significant associations between autonomic functioning and psychopathy and aggression. Conclusion These null-findings highlight the importance of research in naturalistic samples in addition to research in clinical and general populations samples and underscore the complexity of translating research findings into practical and clinical implications.